2012
DOI: 10.1177/0734282912453125
|View full text |Cite
|
Sign up to set email alerts
|

Structural Validity of the Polish Adaptation of the Picture-Based Value Survey for Children (PBVS-C)

Abstract: Recent years have witnessed an increasing number of studies, also in the field of educational psychology, on values within the framework proposed by Schwartz, involving younger and younger respondents. A fresh impetus to studies on children’s values was given by the Picture-Based Value Survey for Children (PBVS-C), which was developed by Döring and her colleagues. This article presents the development and structural validation of the Polish version of the PBVS-C, which measures Schwartz’s four higher-order val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
(23 reference statements)
0
13
0
1
Order By: Relevance
“…Cieciuch et al . () adapted it to Polish and established the structural and construct validity of the German and Polish versions of the PVBS‐C through convergence of findings with the PVQ (Cieciuch et al ., ,b; Döring et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cieciuch et al . () adapted it to Polish and established the structural and construct validity of the German and Polish versions of the PVBS‐C through convergence of findings with the PVQ (Cieciuch et al ., ,b; Döring et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…() developed the PBVS‐C, which they administered to middle childhood samples of German and Polish children. They too found that value structures were largely in line with Schwartz's circular model (Bilsky et al ., ; found eight distinct values, Cieciuch et al ., , ,b found seven distinct values, and Döring et al ., found ten distinct values) . In all value structures, the oppositions between the higher order values of self‐transcendence vs. self‐enhancement and of conservation vs. openness to change were present.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations